The Manifestation of Akhlaq al-Karimah in Muslim Teacher Educators: A Philosophical Inquiry - Abid, Nuskhan; Hartono, Rudi; Haryanti, Rahayu Puji; Pratama, Hendi (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2026)
Amid the ontological challenges of modern higher education, which tends to separate general knowledge from spiritual values, there is an urgent need to understand how moral and religious integrity are integrated into educators' professional identity. The integration of academic professionalism and Islamic ethical values is crucial to addressing the dichotomy of knowledge that often arises in current higher education practices. This study aims to conduct a philosophical inquiry into the embodiment of ethical values in the professional praxis of educators at an Islamic University. Furthermore, this study aims to uncover the meaning of the manifestation of Akhlaq al-Karimah of Muslim teacher educators through philosophical inquiry. This study uses a narrative inquiry design to explore the lived experiences of Muslim educators. Data analysis uses Foucault's technologies of the self. The results show that educators engage in internalizing Divine Trust and Intentionality. Another finding is that Akhlaq al-Karimah manifests as Inner Asceticism and social and pedagogical interactions. Theoretically, this study contributes to the integration of knowledge, with no dichotomy between general knowledge and religion. In practice, the findings can serve as policy recommendations for developing the identity of teacher educators at Islamic universities and integrating Islamic values into professional practice.